Effect of Hydrostatic Pressure Processing Combined with DMDC and Nisin Treatment on the Quality of Bayberry Juice during Storage - Zhouyang SHENG; Bo ZOU; Gengsheng XIAO; Yujuan XU; Jijun WU; Yuanshan YU; Lina CHENG; Jing WEN; Kejing AN (Shipin gongye ke-ji)
In order to enhance the sterilization effect of hydrostatic pressure processing (HPP) on bayberry juice, the effects of thermal sterilization (90 ℃, 5 min), HPP treatment (500 MPa, 5 min), HPP combined antimicrobial agent treatment (HPP combined with dimethyl dicarbonate (DMDC), HPP combined with nisin, and HPP combined with both DMDC and nisin) on microbial population, chromaticity, anthocyanin, polymeric pigment, browning degree, total flavonoid, total phenolics, and volatile compounds of bayberry juice during storage at 4 ℃ were compared. The results showed that HPP treatment alone had limited sterilizing effect on bayberry juice. After 10 d of storage, the total number of colonies in bayberry juice exceeded 100 CFU/mL, which violated the national food safety standard. The quantity of microorganisms of bayberry juice treated with TS and HPP combined antimicrobial agent still met the national standard of food safety after 40 d storage at 4 ℃. During the storage, the anthocyanin content of bayberry juice in different treatment groups showed a decreasing trend, whereas the polypigment and browning degree kept increasing. Meanwhile, the total flavonoid and total phenolic contents decreased first and then increased, while the color difference did not change significantly. The polymerized pigment, total anthocyanin, browning degree, and total phenolic content of TS group were lower than those of the HPP treatment group and the HPP combined antimicrobial agent treatment group during 40 d storage, and no obvious difference was observed among the parameters of the non-thermal-sterilized groups. After 40 d of storage, the content of volatile components decreased in all groups compared to unpasteurized bayberry juice, with no significant difference between thermal sterilization group and the non-thermal-sterilized groups. However, the non-thermal-sterilized bayberry juice better retained two positive flavor substances namely linalool (rose aroma) and 2-pentylfuran (green aroma). The total OVA contribution in the heat-treated group after 40 d of storage was lower than that in the HPP treated group and the HPP combined antimicrobial agent treated group, indicating greater loss of aroma due to thermal treatment. Principal component analysis (PCA) allowed the distinguishment of differences in volatiles among the original juice, heat-sterilized group and non-heat-sterilized group. And the four groups of non-thermal-sterilized bayberry juice were close to each other, indicating that the use of antimicrobial agents did not significantly affect the flavor of bayberry juice in the later stages of storage. In summary, DMDC and nisin can improve the sterilizing effect of HPP on bayberry juice, extending its shelf life, and better maintaining the quality of bayberry juice. The results can provide theoretical basis for non-thermal processing of bayberry juice.